Screening of antagonistic bacteria for controlling Cercospora coffeicola in Arabica coffee - Sirinunta, A.; Akarapisan, A. (International Journal of Agricultural Technology, 2015)
Brown eye spot disease caused by Cercospora coffeicola were collected from Omkoi district, Chiang Mai, Thailand. Thirty isolates of antagonistic bacteria were obtained from rhizosphere of coffee plant. The isolates were purified and assay to inhibit growth of the C. coffeicola. The antagonistic bacteria isolates A74 and A75 showed the highest percentage of growth inhibit against C. coffeicola with 58.33% and 61.67% respectively. Based on the morphological and biochemical properties, isolate A74 and A75 were identified to be a Bacillus megaterium and Bacillus badius respectively. Isolates A74 and A75 were developed for the powder formulation, contained 20 ml of cell bacteria suspension were mixed with 43.5 g of rice flour, 1.5 ml of rice bran oil, 5 g of sucrose. After that, the mixture completely were oven dried at 45◦C for 12 hr and then bio-product were blender to form a powder. The antagonistic bacteria in bio-product can survive for more than 3 months under storage at room temperature. The efficacy for controlling leaf spot disease of bio-product in a greenhouse was tested. The result showed that the disease severity was reduced when spraying with A74 or A75 for 24 hr before or after the pathogen inoculation on coffee leaf. Therefore, bio-product A74 or A75 as a potential biological control agent against C. coffeicola in seedling.